Compact actively Q-switched laser for sensing applications. (March 2021) - Lei, Xinyue; Wieschendorf, Christoph; Hao, Lu; Firth, Josiah; Silvestri, Leonardo; Gross, Simon; Ladouceur, Francois; Withford, Michael; Spence, David; Fuerbach, Alex
Graphical abstract: Highlights: Active Q-switching of an integrated waveguide chip laser using a deformed helix ferroelectric liquid crystal cell is demonstrated. A laser pulse width of 38 ns and a maximum slope efficiency of 22% are obtained using a driving electrical signal with a pulse duration of 2 μs. The laser cavity length is reduced to 250 mm for the compact and portable sensing applications. Abstract: Current active Q-switching is mainly generated by acousto-optical modulators (AOMs) or electro-optical modulators (EOMs). However, EOMs make the setup bulky, while AOMs require the radiofrequency (RF) signal and water-cooling. We present a novel approach to active Q-switching of an integrated waveguide chip laser by utilizing a deformed helix ferroelectric liquid crystal cell (6mm × 6mm) with a thickness of 2 mm. This device can be directly integrated onto the Ytterbium-doped waveguide chip and controlled by the electrical signal. In experiments, with an electrical signal with a pulse duration of 2 μs and a magnitude from 10 V to 84 V, the Q-switched lasers can be observed at a repetition rate ranging from 0.1 kHz to 20 kHz. The shortest pulse duration and the maximum slope efficiency is 38 ns and 22% respectively. This novel integrated and low-cost laser source is a promising tool for a broad range of applications such as gas sensing and LIDAR.